2022
DOI: 10.3389/fvets.2022.782486
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Pain and Analgesia Effectiveness Following Routine Castration in Rabbits Using Behavior and Facial Expressions

Abstract: Prevention of pain in rabbits is a priority for both welfare and validity of scientific data. We aimed to determine if the rabbit grimace scale (RbtGS) could be used as a viable, rapid assessment tool in two breeds of rabbit, Dutch belted (DB) and New Zealand white (NZW), following orchidectomy, as an adjunct to behavioral analysis. All animals received analgesia. Rabbits were filmed and their behavior was recorded at multiple time points pre- and post-orchidectomy. Observers then scored specific pain associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The videos of the 58 animals were edited by the main researcher of the study to generate 2-to-3-minute videos that proportionally represented the duration and frequency of the behaviours observed in the original videos. This edition was based on the ethogram recorded in the three previous studies [ 11 , 12 , 28 ]. For example, if the rabbit was lying down for 5 minutes during the 15-minute original footage (1/3 of the time), edits were performed to guarantee that the rabbit was lying down for 1 minute of the 3-minute video clip (1/3 of time).…”
Section: Methodsmentioning
confidence: 99%
“…The videos of the 58 animals were edited by the main researcher of the study to generate 2-to-3-minute videos that proportionally represented the duration and frequency of the behaviours observed in the original videos. This edition was based on the ethogram recorded in the three previous studies [ 11 , 12 , 28 ]. For example, if the rabbit was lying down for 5 minutes during the 15-minute original footage (1/3 of the time), edits were performed to guarantee that the rabbit was lying down for 1 minute of the 3-minute video clip (1/3 of time).…”
Section: Methodsmentioning
confidence: 99%
“…This is consistent with a pharmacokinetic study that showed that 1 mg/kg in rabbits may be necessary to achieve concentrations considered analgesic in horses (Fredholm et al., 2013 ; Toutain & Cester, 2004 ). In a more recent study, however, it was shown that even a lower dose of meloxicam (0.6 mg/kg) resulted in reduced signs of pain compared to meloxicam administered at 0.2 mg/kg in rabbits undergoing neuter (Miller et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to their limited expressivity and their natural attitude to hide discomfort, pain recognition and treatment have been historically challenging in this species (Benato et al., 2019 ). However, over the last decade, several tools have been developed to assist in evaluating pain in rabbits (Banchi et al., 2022 ; Haddad et al., 2022 ; Keating et al., 2012 ; Miller et al., 2022 ). Among these, the Bristol Rabbit Pain Scale (BRPS) relies on parameters outside facial observations (Benato et al., 2021 ), and it has been shown to be a clinically useful, valid and reliable tool for quantifying pain in rabbits (Benato et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Regular welfare assessments can improve the prospect of detecting signs of pain or distress rapidly, consistently, and accurately, so appropriate intervention, such as timely administration of pain relief, is achieved [ 19 ]. In research, accurate welfare assessment can mean better detection if an intervention has an impact on animal well-being [ 35 , 36 ]. The routine assessment of animal welfare for research purposes supports the collection of high-quality scientific data [ 6 ].…”
Section: Introductionmentioning
confidence: 99%